The impact of instruction based on Toulmin elements on the writing performance of NNES learners / Amirah Dent - Amirah, Dent (2018)
This mixed methods study examined and analysed the impact of instruction based on Toulmin elements on the argumentative writing performance of four NNES learners and uncovered their perspectives on how the instruction of reasoning elements influenced their argumentative essays. The objective of this study was to a) assess the argumentative essays produced by NNES learners to find problems that occur during their writing performance, b) to determine to what extent the instruction based on The Toulmin Model of Argument affect the NNES learners’ argumentative writing performance, and c) to uncover the NNES learners’ perspectives on how the instruction of Toulmin elements impact their argumentative essays. The findings of the study will benefit the NNES learners in relation to their need to improve their argumentative skills in their academic writing. This study used the convergent parallel mixed methods design which involved the collection of quantitative and qualitative data. The two sets of data were then compared and analysed to yield an overall interpretation of results. Four NNES learners participated in the eight-week long study and were asked to produce argumentative essays from the pre-, post-, and delayed post-tests. The argumentative essays were then coded for presence of Toulmin elements. Additionally, the essays were assessed for reasoning quality using an argumentative writing scoring rubric adapted from Qin and Karabacak (2010). The quantitative findings revealed that some Toulmin elements were not present in the participants’ pre-test essays and exposed several problems in the quality of their argumentative essays. After receiving instruction, the NNES learners employed Toulmin elements in the argumentative essays produced in the post- and delayed post-test and had shown improvement in their use of the reasoning elements. The assessments also revealed that the argumentative essays from the post- and delayed post-test contained more rich and complex reasoning compared to the argumentative essays written in during the pretest. The qualitative results revealed that during the early stages of the instruction, they perceived the Toulmin elements data, qualifier, and rebuttal challenging to comprehend and apply in their argumentative essays. Nevertheless, further instruction of Toulmin elements facilitated their understanding of the reasoning features, their function, and application. The semi-structured interview revealed that the NNES learners found the instruction of Toulmin elements useful to their argumentative writing due to several factors. The conclusion of this study recommended that argumentative writing models and reasoning features must be introduced to NNES learners at an earlier stage in order for them to achieve an expected standard of reasoning required in tertiary education levels.